Impact of "Normale" Educational Centre A Significant Factor in the Development of Education in Albania - Sota, Jani (Mediterranean Journal of Social Sciences, 2012)
The history of education has valued preciously all people involved in it and has flourished into an educational function,teaching and learning of our thorough knowledge in its institutions - such as "Normale" Educational center that played an historic role inthe Albanian language. Albanian normal schools have a record of long, difficult, but also glorious path. They were the main homes forgenerations of teachers and also the place where it was necessary to prepare the framework for education and awareness of thenation. Albanian teachers, in different periods of history had run the greatest risk of extinction of national culture and education. Theyplanted the sound seeds by which had brought the essence of national awareness, which in a century struggle of unparalleled trials triedto revive education, science, culture and Albania. In the history of Albania teachers and veterans of teaching, wherever they worked andacted, played the leading role, contributed as they could with their valuable works, which undoubtedly served to their students, futureteachers, in raising subsequently the national level of conscience for their learning and teaching.